2020
DOI: 10.3389/fgene.2020.00809
|View full text |Cite
|
Sign up to set email alerts
|

Comparative microRNA Transcriptomes in Domestic Goats Reveal Acclimatization to High Altitude

Abstract: High-altitude acclimatization is a representative example of vertebrates' acclimatization to harsh and extreme environments. Previous studies reported sufficient evidence for a molecular genetic basis of high-altitude acclimatization, and genomic patterns of genetic variation among populations and species have been widely elucidated in recent years. However, understanding of the miRNA role in high-altitude acclimatization have lagged behind, especially in non-model species. To investigate miRNA expression alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 156 publications
(115 reference statements)
1
13
0
Order By: Relevance
“…The result indicated that tissue differentiation may precede species differentiation, which was consistent with previous studies ( Necsulea and Kaessmann, 2014 ; Hao et al, 2019 ). However, the samples of heart and muscle from each species were more similar than the same tissue between different species (species-specific expression pattern), which reflects striated muscular tissues may have similar expression profiles ( Merkin et al, 2012 ; Tang et al, 2017 ; Feng et al, 2020 ) ( Figure 1A ). In addition, our expression profiles suggested that the differences in global gene expression among tissues were more significant than that among altitudes or the same tissue of different species, which was consistent with the results of previous studies ( Necsulea and Kaessmann, 2014 ; Tang et al, 2017 ; Hao et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The result indicated that tissue differentiation may precede species differentiation, which was consistent with previous studies ( Necsulea and Kaessmann, 2014 ; Hao et al, 2019 ). However, the samples of heart and muscle from each species were more similar than the same tissue between different species (species-specific expression pattern), which reflects striated muscular tissues may have similar expression profiles ( Merkin et al, 2012 ; Tang et al, 2017 ; Feng et al, 2020 ) ( Figure 1A ). In addition, our expression profiles suggested that the differences in global gene expression among tissues were more significant than that among altitudes or the same tissue of different species, which was consistent with the results of previous studies ( Necsulea and Kaessmann, 2014 ; Tang et al, 2017 ; Hao et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that high-altitude hypoxic environments have an important impact on energy metabolism in animals ( 15 , 20 , 21 ). Similarly, we found many differentially expressed genes and signaling pathways related to glucose and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative miRNA transcriptome analysis of two goat populations at distinct altitudes produced reliable evidence for acclimatization based on miRNA-mRNA interactions in hypoxia-related pathways, including that associated with hypoxia inducible factor 1 (HIF-1). The downregulation of miR-509-3p, miR-3069-1-3p, miR-409-5p, and miR-208-3p, and the upregulation of miR-106a-5p, were reported in the hypoxia-sensitive tissues selected by the authors, including the heart, kidney, liver, muscle, and spleen, confirming that miRNAs have a regulatory role in mechanisms related to high-altitude adaptation (115). The potential target genes of these DE-miRNAs are involved in apoptosis, angiogenesis, DNA damage repair, erythropoiesis, and energy metabolism (115).…”
Section: Environmental Stressmentioning
confidence: 52%
“…The downregulation of miR-509-3p, miR-3069-1-3p, miR-409-5p, and miR-208-3p, and the upregulation of miR-106a-5p, were reported in the hypoxia-sensitive tissues selected by the authors, including the heart, kidney, liver, muscle, and spleen, confirming that miRNAs have a regulatory role in mechanisms related to high-altitude adaptation (115). The potential target genes of these DE-miRNAs are involved in apoptosis, angiogenesis, DNA damage repair, erythropoiesis, and energy metabolism (115). Moreover, the authors demonstrated that miR-106a-5p exerted a negative regulatory effect on angiogenesis by targeting the VEGFR1 (or FLT1) gene, thereby paving the way for further utilization of molecular resources in plateau regions.…”
Section: Environmental Stressmentioning
confidence: 52%
See 1 more Smart Citation